A motion capture system using passive markers - Sementille, Antonio Carlos [UNESP] (2004)
This article describes a marker-based optical tracking system using a single camera for determining the positioning and orientation of the body joints. In this implementation, ARToolkit library as well as an approach was used in order to increase the reliability of a motion capture system by using a simplified anatomical human model.